Alla läser! Empiriska perspektiv på frågan om litteraturens samhälleliga relevans - Olle Nordberg (Dalarna university, 2021)
Imaginative literature in Swedish schools is beset by a conflict of goals. It is initially and generally presented in the curriculum as a resource for personal development, insights into the mindset of other people, and the strengthening of democratic values. However, going further in the official school guidelines this literary orientation is supplanted by an instrumental orientation emphasizing technical reading skills, linguistic proficiency, fact-finding and precise grading criteria. This conflict has been subject to considerable research on a theoretical level. The reading project presented here, by contrast, studies an exceptionally large corpus of 25 teachers and 1 200 students empirically to see how they react to the conflict of goals in five major areas: Legitimation, Learning, Gender and age, Teaching and Valorisation. In this paper, the project design is grounded, presented and combined with a discussion about the relevance - and potential - of literary fiction based on some preliminary results.